Land Use and Land Cover Changes in Tankhuwakhola Watershed, Eastern Hills Nepal - Khatiwada, Shambhu Prasad (The Third Pole: Journal of Geography Education, 2019)
This paper examines land use and land cover changes in the eastern hills in general and Tankhuwakhola watershed in particular. More specifically, it attempts to analyze the spatial pattern of land use and land cover changes in the Tankhuwakhola watershed. Land is an integral part of the local community addressing conservation of water, biodiversity resources, and agricultural activities for improving local livelihoods through diversified activities. Land use can be considered as to reflect the degree of human activities directly related to land and making use of its resources and land cover is defined as the observed bio-physical cover of the watershed. The local communities are involved in land used in various ways, ranging from agriculture, forestry, settlements, and water bodies and so on. It shows that land use and land cover change comprises multidisciplinary in nature. This paper concludes that changes in land cover may reveal a response to a shift in local climatic conditions, increasing assess to road transportation, market integration and adoption of new agricultural crops. For this purpose, the data are collected from different sources, including satellite image and topo-sheet maps.